A New q-Analogue of Bernoulli Polynomials Associated with p-Adic q-Integrals. (12th October 2008) - Jang, Lee-Chae
Abstract : We will study a newq -analogue of Bernoulli polynomials associated withp -adicq -integrals. Furthermore, we examine the Hurwitz-typeq -zeta functions, replacingp -adic rational integersx with aq -analogue[ x ] q for ap -adic numberq with| q − 1 | p < 1, which interpolateq -analogue of Bernoulli polynomials.